Rapidly drying pre-coat adhesive composition
Patent Information
- Application Number
- CN202180091046.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-01-20
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-01-20
AI Technical Summary
[0004]然而,目前现有的预涂式粘合剂存在局限性
Smart Images

Figure BDA0004343206490000031 
Figure BDA0004343206490000101 
Figure BDA0004343206490000102
Abstract
Description
Technical Field
[0001] This invention relates to a fast-acting pre-coated adhesive composition comprising at least one (meth)acrylate component; at least one accelerator; at least one organic peroxide; at least one non-aromatic epoxy resin; and at least one cationic photoinitiator. The weight ratio of the (meth)acrylate component to the non-aromatic epoxy resin is 1:4 to 4:1. The pre-coated adhesive composition of this invention is first applied to the surface of a substrate and allowed to dry with the aid of UV light. Subsequently, after the coated substrate is assembled with a mating substrate, the dried pre-coated adhesive composition undergoes anaerobic curing, providing excellent thread-locking strength and lap shear strength for bonding. Background Technology
[0002] Mechanical locking devices, such as open-end washers and flat washers, are used to address loosening issues in most threaded assemblies. Because mechanical locking devices can operate in varying, even harsh, environments, they do not always maintain clamping force, and assemblies locked with such devices often loosen under vibration, thermal expansion, or inappropriate torque.
[0003] The invention of pre-applied adhesives aims to further prevent loosening of threaded assemblies. Conventional pre-applied adhesives comprise two components. One component includes a polymerizable monomer, and the other includes a polymerization initiator encapsulated in microcapsules. These two components are mixed before use and applied to a substrate, such as the threads of a bolt. After drying, the pre-applied adhesive forms a dry film on the threaded substrate. Following assembly of the threaded substrate coated with the dry film to a mating substrate, the dry film undergoes further anaerobic curing.
[0004] However, existing pre-coated adhesives have limitations. If the pre-coated adhesive is water-based, the drying time to form a dry film is long, and it is not easy to use on threaded substrates. If the pre-coated adhesive is solvent-based, the drying time is shorter, but the solvent is environmentally harmful.
[0005] Therefore, there is a need to develop a new type of pre-coated adhesive with a shorter drying time and good bonding strength. Summary of the Invention
[0006] This invention relates to a pre-coated adhesive composition comprising:
[0007] a) At least one (meth)acrylate component;
[0008] b) At least one accelerator;
[0009] c) At least one organic peroxide;
[0010] d) at least one non-aromatic epoxy resin; and
[0011] e) At least one cationic photoinitiator
[0012] The weight ratio of the (meth)acrylate component to the non-aromatic epoxy resin is 1:4 to 4:1.
[0013] The present invention also relates to a method for preparing a pre-coated adhesive composition.
[0014] The present invention also relates to a method for curing a pre-coated adhesive composition. With the aid of UV light, the pre-coated adhesive composition can be rapidly dried to form a dry film.
[0015] The present invention also relates to a dry film formed from the pre-coated adhesive composition.
[0016] The present invention also relates to a cured product of a pre-applied adhesive composition. The cured product of the pre-applied adhesive composition provides excellent thread-locking strength and lap shear strength for bonding.
[0017] The present invention also relates to an article bonded or coated with a dry film or cured product of a pre-coated adhesive composition. Detailed Implementation
[0018] The invention is described in more detail in the following paragraphs. Each aspect thus described may be combined with any other aspect or aspects unless expressly indicated to the contrary. In particular, any feature indicated as preferred or advantageous may be combined with any other feature indicated as preferred or advantageous.
[0019] In the context of this invention, unless the context otherwise requires, the terminology used will be interpreted according to the following definitions.
[0020] As used herein, the singular forms “a,” “an,” and “the” include both the singular and plural forms unless the context clearly indicates otherwise.
[0021] The terms “comprising,” “including,” and “containing” are used in this document and are inclusive or open-ended, not excluding additional unstated ingredients, elements, or process steps.
[0022] The description of numerical endpoints includes all numbers and fractions within the corresponding range, as well as the described endpoints.
[0023] All references cited in this specification are incorporated herein by reference in their entirety.
[0024] Unless otherwise defined, all terms used in this disclosure, including technical and scientific terms, shall have the meanings commonly understood by one of ordinary skill in the art to which this invention pertains. Definitions of terms are included by way of further instruction to better understand the teachings of this invention.
[0025] In the context of this invention, many terms should be used.
[0026] The term "dry film" refers to a solid film that is non-sticky to the touch and meets the ASTM C679 test criteria. The dry film of this invention can be obtained by using a pre-coated adhesive composition cured with UV light.
[0027] The term "cured product of a pre-applied adhesive composition" refers to a cured product that can be obtained from the pre-applied adhesive composition after UV curing and anaerobic curing.
[0028] The term "(meth)acrylate" refers to both or either "acrylate" or "methacrylate".
[0029] The term "monomer" refers to a polymer building block that has a specific molecular structure and can react to form part of a polymer.
[0030] The terms “polymer” and “resin” are used interchangeably and include resin, oligomer, and polymer, referring to a macromolecule composed of at least two monomer units.
[0031] The term "hydrocarbon group" refers to an organic compound composed of carbon and hydrogen. Examples of hydrocarbon groups include, but are not limited to, alkyl groups, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, isopropyl, tert-butyl, isobutyl, etc.; alkenyl groups, such as vinyl, allyl, butenyl, pentenyl, hexenyl, etc.; aralkyl groups, such as benzyl, phenethyl, 2-(2,4,6-trimethylphenyl)propyl, etc.; or aryl groups, such as phenyl, tolyl, xylyl, etc.
[0032] The term "epoxy resin" refers to an epoxy compound whose molecular structure contains at least one epoxy group.
[0033] The term "non-aromatic epoxy resin" refers to epoxy resins whose molecular structure does not contain conjugated aromatic rings.
[0034] (meth)acrylate component
[0035] The pre-applied adhesive composition of the present invention comprises at least one (meth)acrylate component, said (meth)acrylate component comprising at least one group having the following general formula:
[0036]
[0037] In equation (1), R represents hydrogen, halogen, or optionally substituted C1-C. 20 Monovalent hydrocarbon group. Preferably, R is hydrogen or an optionally substituted C1-C group. 10 Monovalent hydrocarbon group. This (meth)acrylate component can be used alone or in combination.
[0038] The (meth)acrylate component of the present invention can exist in the form of a monomer, a polymer, or a combination thereof. When in polymer form, the (meth)acrylate component can be a chain attached to at least one group of formula (1). The (meth)acrylate component can have a chain composed of polyethylene, polyether, polyester, polyurethane, polyamide, vinyl ester, phenolic resin, amino resin, etc. The group of formula (1) can be located on the side chain or at the end position of the main chain, or a combination thereof. Preferably, the (meth)acrylate component has at least two groups of formula (1) at the end position.
[0039] Exemplary (meth)acrylate monomers include isobornyl acrylate (IBOA), isobornyl methacrylate (IBOMA), tetrahydrofurfuryl acrylate (THFA), (5-ethyl-1,3-dioxane-5-yl)methyl acrylate, cyclohexyl acrylate, cyclohexyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, tert-butylcyclohexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, phenyl acrylate, phenyl methacrylate, benzyl acrylate, benzyl methacrylate, phenethyl acrylate, phenethyl methacrylate, and dicyclopentanyl acrylate. Acrylates, 3,3,5-trimethylcyclohexyl acrylate, 3,3,5-trimethylcyclohexyl methacrylate, dicyclopentenyl acrylate, 1,6-hexanediol diacrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-nonyl acrylate, n-decyl acrylate, isooctyl acrylate, n-dodecyl acrylate, n-tridecyl acrylate, n-hexadecyl acrylate, n-stearyl acrylate, isomalmityl acrylate, and isostearyl acrylate (ISTA). (Meth)acrylate monomers can be used alone or in any combination.
[0040] Exemplary (meth)acrylate polymers include polyurethane (meth)acrylate polymers, polyisoprene (meth)acrylate polymers, polybutadiene (meth)acrylate polymers, polyester (meth)acrylate polymers, and polyether (meth)acrylate polymers. (Meth)acrylate polymers may be used alone or in combination.
[0041] Examples of commercially available (meth)acrylate components include, for example, SR531, SR508, and SR285 from Sartomer; BR-3641AJ, BR3741AJ, BR-3641AA, BR-345, BR-543, BR-571MB, BR-742M, BRC-443, BRC-443D, BRC-843, BRC-843S, BRC-843D, BR7432GB, BR-641D, BR-641S, BR-744BT, and BR-744SD from Dymax Polymers & Coatings; and those from Allnex Group. EBECRYL230, EBECRYL-231, EBECRYL-242, EBECRYL-244, EBECRYL-246, EBECRYL-4491, EBECRYL4483, EBECRYL-8841, EBECRYL-8804 and EBECRYL-6603 from Companies; Visiomer HEMA 97 from Evonik.
[0042] In some embodiments of the invention, the amount of (meth)acrylate component is preferably 5 to 90% by weight, more preferably 20 to 80% by weight, and even more preferably 40 to 70% by weight, based on the total weight of the pre-coated adhesive composition.
[0043] Accelerator
[0044] The pre-coated adhesive composition of the present invention comprises at least one accelerator to accelerate the polymerization of the (meth)acrylate component under anaerobic conditions. Suitable accelerators include, but are not limited to, thioimides (e.g., saccharin and its derivatives), tertiary amines (e.g., N,N-diethyl-p-toluidine, N,N-dimethyl-o-toluidine, N,N-dimethylaniline, N,N-diethylaniline, p-isopropyl-N,N-dimethylaniline, N,N-dimethyl-p-toluidine, 2,4-dimethyl-N,N-dimethylaniline, 3,5-dimethyl-N,N-dimethylaniline), and hydrazine or acylhydrazine derivatives (e.g., sulfonyl hydrazine, acetyl-2-phenylhydrazine (APH), and p-toluenesulfonyl hydrazine). The accelerator may be used alone or in any combination.
[0045] In some embodiments of the invention, the pre-coated adhesive composition preferably contains at least one thioimide as an accelerator, and more preferably contains both saccharin and acetyl-2-phenylhydrazine as accelerators.
[0046] Examples of commercially available accelerators include saccharin from Dow Chemical; acetyl-2-phenylhydrazine from Sigma Aldrich; and N,N-diethyl-p-toluidine from Sigma Aldrich.
[0047] In some embodiments of the invention, the amount of accelerator is 0.1 to 5% by weight, more preferably 0.1 to 2% by weight, and even more preferably 0.1 to 0.5% by weight, based on the total weight of the pre-coated adhesive composition.
[0048] Organic peroxides
[0049] The pre-coated adhesive composition of the present invention comprises at least one UV-insensitive organic peroxide as an initiator to initiate the polymerization of the (meth)acrylate component under anaerobic conditions. Suitable organic peroxides include, but are not limited to, dicumyl peroxide (DCP), benzoyl peroxide (BPO), di-tert-butyl peroxide and 2,5-dimethyl-2,5-bis(tert-butylperoxy)-hexyne (DBPH), di(2,4-dichlorobenzoyl peroxide) (DCBP), 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, and organic hydroperoxides (e.g., cumene hydroperoxide (CHP), tert-butyl hydroperoxide (TBH), methylethyl ketone hydroperoxide, and dicumyl hydroperoxide). The organic peroxide can be used alone or in combination. In some embodiments of the present invention, organic hydroperoxides are preferred.
[0050] Examples of commercially available organic peroxides include, for example, DCP from Taicang Plastic Additive Co., Ltd.; DCP-40 from Jiangsu Daoming Chemical Co., Ltd.; Varox 231XL from Vanderbilt Chemicals, LLC; TMCH-40 from United Initiators Inc.; and Luperox CU90 and KC70 from Arkema.
[0051] In some embodiments of the invention, the amount of organic peroxide is 0.1 to 3% by weight, preferably 0.1 to 0.5% by weight, based on the total weight of the pre-coated adhesive composition.
[0052] Non-aromatic epoxy resin
[0053] The pre-applied adhesive composition of the present invention comprises at least one non-aromatic epoxy resin. Suitable non-aromatic epoxy resins include, but are not limited to, aliphatic epoxy resins (e.g., propylene glycol-diglycidyl ether and pentaerythritol-polyglycidyl ether), alicyclic epoxy resins (e.g., 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate and bis(3,4-epoxycyclohexylmethyl)adipate), and heterocyclic epoxy resins (e.g., triglycidyl isocyanurate). The non-aromatic epoxy resin may be used alone or in combination.
[0054] Examples of commercially available non-aromatic epoxy resins include, for example, Araldite CY179, 184, and 192 from Ciba Specialty Chemicals; EHPE-3150 from Daicel Chemical Industries, Ltd.; and Syna-Epoxy S21, 27, and 28 from Nantong Synasia New Material Co., Ltd.
[0055] In some embodiments of the invention, the amount of non-aromatic epoxy resin is 20 to 70% by weight, preferably 30 to 50% by weight, based on the total weight of the pre-coated adhesive composition.
[0056] Surprisingly, it was found that when the weight ratio of the (meth)acrylate component to the non-aromatic epoxy resin was between 1:4 and 4:1, this pre-coated adhesive composition could form a suitable dry film on the substrate very quickly after UV curing, with sufficient elasticity. If the weight ratio was outside this range, the film was either too stiff or too wet to be used for subsequent assembly of the coated substrate with the mating substrate. When the film was too stiff, it lacked sufficient elasticity, causing the coated substrate to be unable to be assembled with the mating substrate, especially when the coated substrate was a bolt and the mating substrate was a nut. When the film was too wet, it tended to sag or flow over time, making the adhesive composition unsuitable for use as a pre-coated adhesive.
[0057] In some embodiments of the invention, the weight ratio of the (meth)acrylate component to the non-aromatic epoxy resin is more preferably 1:2 to 3:1. In other embodiments of the invention, the weight ratio of the (meth)acrylate component to the non-aromatic epoxy resin is even more preferably 2:1 to 3:1, such that the cured product of the pre-applied adhesive composition has better thread locking strength and lap shear strength.
[0058] It was also found that if epoxy resins containing conjugated aromatic rings in their molecular structure are used, the film formed on the substrate after UV curing is too hard to be used for subsequent assembly of the coated substrate with the mating substrate.
[0059] cationic photoinitiator
[0060] The pre-coated adhesive composition of the present invention comprises at least one cationic photoinitiator to initiate the polymerization of a non-aromatic epoxy resin. The cationic photoinitiator forms an excited state upon irradiation, and then the excited state decomposes to release free radical cations. These free radical cations react with a hydrogen atom donor to generate a protic acid, which initiates a crosslinking reaction.
[0061] The most commonly used cationic photoinitiators are organohalonium salts, iodonium salts, or sulfonium salts. In some embodiments of the invention, organoiodonium salts or sulfonium salts are preferably incorporated into the pre-coated adhesive composition. The anions in these salts typically have low nucleophilicity and include, but are not limited to, SbF6, PF6, AsF6, BF4, B(C6F5)4, or Ga(C6F5)4. Iodonium salts may be selected from, for example, diaryliodonium hexafluorophosphate, diaryliodonium hexafluoroantimonate, diaryliodonium tetra(pentafluorophenyl)borate, 4-octoxyphenylphenyliodonium hexafluoroantimonate, 4-(2-hydroxytetradecyloxyphenyl)phenyliodonium hexafluoroantimonate, and 4-(1-methylethyl)phenyl-4-methylphenyliodonium tetra(pentafluorophenyl)borate. The sulfonium salt can be selected from, for example, diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate, triarylsulfonium hexafluorophosphate, and triarylsulfonium hexafluoroantimonate. This cationic photoinitiator can be used alone or in combination.
[0062] Examples of commercially available cationic photoinitiators include, for example, Irgacure 290 from BASF; UVI-6976 and 6992 from NantongSynasia New Material Co., Ltd; and Cyracure UVI9676 from Dow Chemicals.
[0063] In some embodiments of the invention, the amount of cationic photoinitiator is 0.2 to 4% by weight, preferably 0.5 to 1.5% by weight, based on the total weight of the pre-coated adhesive composition.
[0064] Optional additives
[0065] The pre-applied adhesive composition may also contain optional additives. The selection of suitable additives for the pre-applied adhesive composition of the present invention depends on the specific intended use of the pre-applied adhesive and can be determined by those skilled in the art in each case.
[0066] Stabilizer
[0067] The pre-applied adhesive compositions of the present invention may optionally contain at least one stabilizer to control and prevent premature peroxide decomposition and polymerization of the compositions. Suitable stabilizers include, but are not limited to, phenols (e.g., hydroquinone and tetrahydroquinone), quinones (e.g., naphthoquinone and anthraquinone), and chelating agents (e.g., tetrasodium salts and β-ketoesters of ethylenediaminetetraacetic acid (“EDTA”). Stabilizers may be used alone or in combination.
[0068] In some embodiments of the invention, the amount of stabilizer is 0 to 2% by weight, preferably 0.1 to 1% by weight, based on the total weight of the pre-coated adhesive composition.
[0069] Fumed silica
[0070] The pre-coated adhesive composition of the present invention may optionally contain at least one fumed silica to adjust the thixotropic and thickening properties of the composition.
[0071] Examples of commercially available fumed silica include, for example, CAB-O-SIL M-5 from Cabot Corporation and AEROSIL R 974 from Evonik Specialty Chemicals (Shanghai) Co., Ltd.
[0072] In some embodiments of the invention, the amount of fumed silica is preferably 0 to 5% by weight, more preferably 0.1 to 3% by weight, based on the total weight of the pre-coated adhesive composition.
[0073] Other optional additives that can be used in the pre-coated adhesive compositions of the present invention include, but are not limited to, biocides, dyes, pigments and mixtures thereof.
[0074] In a preferred embodiment, the pre-applied adhesive composition comprises:
[0075] (a) 5 to 90% by weight of at least one (meth)acrylate component;
[0076] (b) 0.1 to 0.5% by weight of at least one accelerator;
[0077] (c) 0.1 to 0.5% by weight of at least one organic peroxide;
[0078] (d) 20 to 70% by weight of at least one non-aromatic epoxy resin; and
[0079] (e) 0.5 to 1.5% by weight of at least one cationic photoinitiator;
[0080] in
[0081] The sum of the weight percentages of all components equals 100% by weight; and
[0082] The weight ratio of the (meth)acrylate component to the non-aromatic epoxy resin is 1:4 to 4:1.
[0083] Those skilled in the art will be able to make appropriate selections among the various components based on the description, representative embodiments and guidance of the present invention to prepare compositions that can achieve the desired effects.
[0084] The pre-coated adhesive composition of the present invention can be prepared by uniformly mixing all components together, and preferably by the following steps:
[0085] a) Mix all components together except for the organic peroxide and the cationic photoinitiator;
[0086] b) Add at least one organic peroxide and at least one cationic photoinitiator to the mixture of step a); and
[0087] c) Further mix all components uniformly to obtain the pre-coated adhesive composition.
[0088] Throughout the adhesive preparation process, the temperature is preferably controlled below 50°C.
[0089] A variety of substrates are suitable for coating with the pre-coated adhesive composition of the present invention. Suitable substrates may be made of steel, brass, copper, aluminum, zinc, and other metals and alloys. The pre-coated adhesive composition can be applied to the substrate by brush, scraper, sprayer, dispenser, or extruder, and allows for initial UV curing to form a dry film on the substrate surface. The substrate coated with the dry film can be assembled onto a mating substrate immediately after the dry film is formed, and the pre-coated adhesive composition can be further anaerobic cured. Optionally, if the mating substrate is not yet ready, the substrate coated with the dry film can be stored at an indoor environment (23°C and 50% RH) for at least 7 days and assembled with the mating substrate once it is ready.
[0090] In some embodiments, it is preferable to apply the pre-coated adhesive composition to the substrate and cure it by means of the following steps:
[0091] a) Provide the substrate;
[0092] b) Apply the pre-coated adhesive composition to the surface of a substrate to create an adhesive layer;
[0093] c) Irradiate the adhesive layer with UV light to obtain a dry film;
[0094] d) Assemble the dry-film coated substrate with the matching substrate and create an anaerobic environment; and
[0095] e) Anaerobic curing of the dry film.
[0096] The dry film formed from the pre-coated adhesive composition of the present invention has a non-sticky surface and sufficient elasticity for subsequent assembly processes. Preferably, the Shore D hardness of the dry film is 15 to 40, as measured according to ISO 868.
[0097] The cured products of the pre-coated adhesive components obtained after curing the pre-coated adhesive composition via UV curing and anaerobic curing exhibit excellent thread-locking strength and lap shear strength. Preferably, the cured product has a breaking torque of 11 to 22 N*m as measured according to ISO 10964 and an lap shear strength of 6 to 11 N / mm as measured according to ISO 4587. 2 .
[0098] Example:
[0099] The present invention will be further described and illustrated in detail below with reference to the embodiments. These embodiments are intended to help those skilled in the art better understand and practice the invention, but are not intended to limit the scope of the invention. Unless otherwise stated, all figures in the embodiments are based on weight.
[0100] Examples 1-16
[0101] The following materials were used in the examples.
[0102] Bomar BR-543 (a bifunctional aliphatic polyether urethane acrylate available from Dymax);
[0103] Bomar BR-571MB (a bifunctional aliphatic polyether urethane methacrylate available from Dymax);
[0104] Bomar BR-742M (a bifunctional aliphatic polyester urethane methacrylate available from Dymax);
[0105] Visiomer HEMA 97 (2-hydroxyethyl methacrylate, available from Evonik);
[0106] Saccharin (available from Dow Chemical);
[0107] APH (acetyl-2-phenylhydrazine, available from Sigma Aldrich);
[0108] CHP (cumene hydroperoxide, available from SCRC);
[0109] Syna-Epoxy S21 (3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, available from Nantong Synasia New Material Co., Ltd.), has the following structure:
[0110]
[0111] Syna-Epoxy S28 (bis(3,4-epoxycyclohexylmethyl) adipate, available from Nantong Synasia New Material Co., Ltd.), has the following structure:
[0112]
[0113] UVI 6976 (diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate, available from Nantong Synasia New Material Co., Ltd.), has the following structure:
[0114]
[0115] Using the components and corresponding weight percentages according to Tables 1a and 1b, a sample of a pre-coated adhesive composition was prepared as an example (Ex.) by following these steps:
[0116] a) Mix Bomar BR-543 / BR-571MB / BR-742M, Visiomer HEMA 97, saccharin, APH and Syna-Epoxy S21 / S28 together at 600 rpm for 30 minutes;
[0117] b) Add CHP and UVI 6976 to the mixture from step a); and
[0118] c) Further mix all components at 600 rpm for 2 hours to obtain a pre-coated adhesive composition sample.
[0119] Throughout the adhesive preparation process, the temperature is controlled at approximately 25°C.
[0120] Various tests were performed on samples of the pre-applied adhesive composition, and the results are shown in Tables 2-4.
[0121] Table 1a. Pre-coated adhesive compositions
[0122]
[0123] Table 1b. Pre-coated adhesive compositions
[0124]
[0125] Test methods
[0126] The pre-coated adhesive composition sample was applied to the surface of an RS-14 mild steel substrate (available from Baiside) by brushing. The thickness of the adhesive layer was controlled to be approximately 0.5 mm.
[0127] Using a Loctite ZETA 7401UV floodlight box, with 365nm UV light at 100mW / cm², 2 The sample adhesive layer was irradiated with UV light for 30 seconds to form a film on the surface of the RS-14 mild steel substrate. After the aforementioned UV curing, the coated RS-14 mild steel substrate was placed in an indoor environment (23°C and 50% RH) for 1 hour, and then used for the following hardness test, surface dryness test and lap shear strength test.
[0128] <Hardness Test>
[0129] The hardness of a film is measured using a Shore D hardness tester (BS 61II, available from Bareiss) according to ISO 868.
[0130] <Surface Dryness Test>
[0131] Inspect the membrane surface according to ASTM C679. Use an acrylic sheet to test the membrane's dryness. If the membrane cannot be lifted with the acrylic sheet, it is considered a dry membrane, and its non-stick surface property is rated "acceptable". Conversely, if the membrane can be lifted with the acrylic sheet, it is not considered a dry membrane, and its non-stick surface property is rated "unacceptable".
[0132] <Overlap Shear Strength>
[0133] A coated RS-14 mild steel substrate was assembled with a matching substrate (RS-14 low-carbon steel substrate available from Baiside) to create an anaerobic environment, which allowed the membrane to be further cured to obtain a cured product of the pre-coated adhesive composition. The membrane was anaerobically cured for 24 hours before lap shear strength testing.
[0134] The lap shear strength of the cured product was measured according to ISO 4587 using a general-purpose testing machine of MTS (model 43) at a bonding speed of 2 mm / min.
[0135] <Thread locking strength>
[0136] The pre-applied adhesive composition sample was applied to the threads of the bolt (M10 black oxide bolts available from Baiside) by immersing the bolt in the adhesive sample. A Loctite ZETA7401 UV floodlight box was used with 365nm UV light at 100mW / cm². 2 The pre-coated adhesive composition sample was irradiated with an intensity of 30 seconds to form a film on the threads of the bolt.
[0137] Following the aforementioned UV curing, the coated bolts were placed in an indoor environment (23°C and 50% RH) for 1 hour and assembled with nuts (soft steel nuts available from Baiside). The assembled bolts and nuts were then placed in an indoor environment (23°C and 50% RH) for 24 hours to allow the film to undergo further anaerobic curing, thereby obtaining the cured product of the pre-coated adhesive composition.
[0138] The bond strength of the cured product was measured according to ISO 10964, including the fracture torque and pull-out torque. The tests were conducted using a torque meter from Hengyi Testing Instrument Co., Ltd. (HY-NZ), with a rotational speed of 60 rpm selected for both fracture torque and pull-out torque measurements.
[0139] Test Results
[0140] Table 2a. Membrane hardness
[0141] Hardness (Shore D hardness) 33 28 24 21 30 24 18 16
[0142] Table 2b. Membrane Hardness
[0143]
[0144] Tables 2a and 2b report the hardness of the films formed from the pre-coated adhesive composition samples. The hardness of the films in Ex. 1 to 14 is acceptable. The film hardness in Ex. 15 is too high, while the film hardness in Ex. 16 is too low.
[0145] Table 3a. Surface dryness of the membrane
[0146]
[0147] Table 3b. Surface dryness of the membrane
[0148]
[0149] Tables 3a and 3b report the surface dryness of the films formed from the pre-coated adhesive composition samples. The films formed in Ex. 1 to 15 are acceptable dry films. The film formed in Ex. 16 is not a dry film and has a sticky surface that may sag or flow over time, making the adhesive composition unsuitable for use as a pre-coated adhesive.
[0150] Table 4a. Overlap shear strength of cured pre-coated adhesive compositions
[0151]
[0152] Table 4b. Overlap shear strength of cured pre-coated adhesive compositions
[0153]
[0154] Tables 4a and 4b report the lap shear strength of the cured products of the pre-applied adhesive composition samples. The lap shear strength of the cured products of the pre-applied adhesive composition sample in Ex. 15 is too low compared to the other examples.
[0155] Table 5a. Thread locking strength of cured pre-coated adhesive compositions
[0156]
[0157] Table 5b. Thread locking strength of cured pre-coated adhesive compositions
[0158] Breaking torque (N*m) 14.7 14.5 19.3 12.5 12.5 13.4 N / A 14.8 Pull-out torque (N*m) 6.3 6.6 10.5 4.5 5.6 6.8 N / A 7.7
[0159] Tables 5a and 5b report the thread-locking strength of the cured products of the pre-coated adhesive composition samples. The thread-locking strength of the cured product of the pre-coated adhesive composition sample in Example 15 could not be measured because the film applied to the bolt was too hard, making it impossible to assemble the bolt with the nut.
Claims
1. A pre-applied adhesive composition comprising: a) At least one (meth)acrylate component; b) At least one accelerator; c) At least one organic peroxide; d) At least one non-aromatic epoxy resin; and e) At least one cationic photoinitiator The weight ratio of the (meth)acrylate component to the non-aromatic epoxy resin is 1:4 to 4:1, and the accelerator comprises both saccharin and acetyl-2-phenylhydrazine.
2. The pre-coated adhesive composition according to claim 1, wherein the (meth)acrylate component is selected from (meth)acrylate monomers, (meth)acrylate polymers, or combinations thereof.
3. The pre-coated adhesive composition according to claim 1 or 2, wherein the non-aromatic epoxy resin is selected from aliphatic epoxy resins, alicyclic epoxy resins, heterocyclic epoxy resins, or any combination thereof.
4. The pre-coated adhesive composition according to claim 1 or 2, wherein the cationic photoinitiator is selected from organohalonium salts, organoiodonium salts, organosulfonium salts, or any combination thereof.
5. The pre-applied adhesive composition according to claim 1 or 2, wherein the amount of the (meth)acrylate component is 5 to 90 by weight based on the total weight of the adhesive composition.
6. The pre-coated adhesive composition according to claim 1 or 2, wherein the amount of the non-aromatic epoxy resin is 20 to 70 by weight based on the total weight of the adhesive composition.
7. The pre-coated adhesive composition according to claim 1 or 2, wherein the weight ratio of the (meth)acrylate component to the non-aromatic epoxy resin is 1:2 to 3:
1.
8. The pre-coated adhesive composition according to claim 1 or 2, wherein the weight ratio of the (meth)acrylate component to the non-aromatic epoxy resin is 2:1 to 3:
1.
9. The pre-applied adhesive composition according to claim 1 or 2, comprising: (a) 5 to 90% by weight of at least one (meth)acrylate component; (b) 0.1 to 0.5% by weight of at least one accelerator; (c) 0.1 to 0.5% by weight of at least one organic peroxide; (d) 20 to 70% by weight of at least one non-aromatic epoxy resin; and (e) 0.5 to 1.5% by weight of at least one cationic photoinitiator, The sum of the weight percentages of all components equals 100% by weight; and The weight ratio between the (meth)acrylate component and the non-aromatic epoxy resin is 1:4 to 4:
1.
10. A method for preparing a pre-applied adhesive composition according to any one of claims 1 to 9, comprising the following steps: a) Mix all components together except for the organic peroxide and the cationic photoinitiator; b) Add at least one organic peroxide and at least one cationic photoinitiator to the mixture of step a); and c) Further mix all components uniformly to obtain the pre-coated adhesive composition. The temperature is controlled below 50℃ during the preparation process.
11. A method for curing a pre-applied adhesive composition according to any one of claims 1 to 9, comprising the following steps: a) Provide the base material; b) Apply the pre-coated adhesive composition to the surface of the substrate to create an adhesive layer; c) Irradiate the adhesive layer with UV light to obtain a dry film; d) The dry-film coated substrate is assembled with a matching substrate to create an anaerobic environment; as well as e) Anaerobically cure the dry film.
12. A dry film formed from any one of the pre-coated adhesive compositions according to claims 1 to 9.
13. A cured product of a pre-applied adhesive composition according to any one of claims 1 to 9.
14. An article coated or bonded with a dry film or cured product of a pre-coated adhesive composition according to claim 13.
Citation Information
Patent Citations
Dual-curable adhesive composition, use thereof, and process for bonding substrates
WO2013067947A1